INFLUENCE STUDENT’S INVOLVEMENT IN EXTRACURRICULAR ORGANIZATION - melania fandika; irwan Suntoro; Yunisca Nurmalisa (Jurnal Kultur Demokrasi, 2012)
Purpose of this research was to determine, analizye and test the effect of student’s involvement in extracurricular organization to student character of SMA Negeri 15 bandar lampung 2012/2013. Method in this research is correlational. Respondent in this research was 55 students. Method of analyze used Chi Kuadrat theory. Result in this research there is a signficant effect between student’s involvement in extracurricular organization to student character of SMA negeri 15 bandar lampung 2012/2013.Key Word: Student’s involvement in extracurriculer organization, student’s character.